PENGARUH SOSIAL BUDAYA TERHADAP KETAHANAN EKONOMI (STUDI KASUS PADA PELAKU EKONOMI SEKTOR INFORMAL DI DUKUH KARANG PADANG, DESA SERUT, KECAMATAN GEDANG SARI, KABUPATEN GUNUNG KIDUL) - Sudaryatie, Sudaryatie (Buletin Ekonomi Manajemen, Ekonomi Pembangunan, Akuntansi, 2017)
The influence of Socio-Culture on Economic Resilience (Case Study on Economic Sector of Informal Sector in Hamlet Karang Padang, Serut Village, Gedang Sari Sub-District, Gunung Kidul Regency). Development can be formulated as a systematic and planned effort to improve the quality of life of people and society in a sustainable manner, utilizing the available resources optimally, efficiently, effectively and accountably, so as to form socio-cultural resilience .. Socio-cultural resilience, can have a direct impact on economic resilience . Socio-cultural resilience has a very close cohesion relationship with economic resilience. This study aims to analyze the common thread between Socio-cultural Resilience, as well as economic Resilience. The author tries to examine the socio-cultural life especially related to the behavior of kinship and social solidarity of the informal economy actors of the people of Karangpadang Hamlet in its contribution to economic resilience in the area of Gunung Kidul Regency of Yogyakarta Province. The result of the analysis shows that the socio-cultural life (in kinship system) of Karangpadang Hamlet, Serut Village, Gedangsari District, Gunungkidul Regency are very strong, they are very concerned in preserving and developing the existing tradition, not the exception of the people working outside the region as economic actors the informal sector. This makes the level of socio-cultural Resilience in this area is very high. The attachment of the informal sector of the informal economy to the regions of origin is very strong, it can be seen from the behavior of those who always bring the results of their work to home areas, both for household purposes and for investment purposes (houses, land, rice fields) and social activities culture (tradition). This will increase the velocity of money in the area of origin and able to bring the welfare of local communities so that the level of Social and Cultural Resilience contribute to the increasing level of Economic Resilience